Relational Database Design for Web-Based Computer Inventory System Jabatan Pelajaran Negeri (JPN) Perak - Shafie, Abd Rashid (2005)
This study was focus on designed database system for web-based computer inventory system for Jabatan Pelajaran Perak namely JPCIS. A methodology is defined for the design of this relational database. The methodology is presented as a systematic guide to the five main phases of database design namely as follows (1) Requirement Analysis, (2) Conceptual Database Design, (3) Logical Database Design, (4) Physical Database Design, and (5) Prototyping. The data requirements are defined and conceptualised using an extended Entity-Relationship Model (ER Model), with the extensions being additional semantics such as relationship, optional relationship, and the generalisation abstractions. There are three categories of users and 15 entities been identified. Cross-Referencing Transaction been used to analyse transactions. The main objective is to understand the functionality of transaction (query) run on the database. In Logical Database Design with involved build and validate local logical design, Data Flow Diagram been drawn to visualized it. Data Flow Diagram been used to analyse transactions. The main objective is to understand the functionality of transaction (query) run on the database. Finally automated prototyping been used to validate the database system and the test shown that it meet the users needs.